Mapping the Potential of the Domestic Tourist Market in Indonesia - Addin Maulana (Conference Series, 2020)
By modifying the quadrant model using secondary data related to the number of domestic tourist trips, GRDP per Capita, Trip Duration, and Average Spending per visit in each province in Indonesia. This research has succeeded in mapping 7 provinces which are categorized as high domestic tourist market categories, including DKI Jakarta, Riau Islands, East Kalimantan, North Kalimantan, Papua, West Papua, and Riau. And, 11 provinces with moderate potential categories, including Central Kalimantan, Gorontalo, Jambi, West Kalimantan, Maluku, North Maluku, East Nusa Tenggara, Central Sulawesi, Southeast Sulawesi, North Sulawesi, and South Sumatra. The Indonesian government needs to optimize these provinces because they are considered capable of providing added economic value to other provinces when traveling.